Spectroscopic investigation of native defect induced electron–phonon coupling in GaN nanowires. (19th June 2017) - Parida, Santanu; Patsha, Avinash; Bera, Santanu; Dhara, Sandip
Abstract: The integration of advanced optoelectronic properties in nanoscale devices of group III nitride can be realized by understanding the coupling of charge carriers with optical excitations in these nanostructures. The native defect induced electron–phonon coupling in GaN nanowires are reported using various spectroscopic studies. The GaN nanowires having different native defects are grown in an atmospheric pressure chemical vapor deposition technique. X-ray photoelectron spectroscopic analysis revealed the variation of Ga/N ratios in nanowires having possible native defects, with respect to their growth parameters. The analysis of the characteristic features of electron–phonon coupling in the Raman spectra show the variations in carrier density and mobility, with respect to the native defects in unintentionally doped GaN nanowires. The radiative recombination of donor acceptor pair transitions and the corresponding LO phonon replicas observed in photoluminescence studies further emphasize the role of native defects in electron–phonon coupling.